Super-Symmetry Quantum Factorization of Radial Schrodinger Equation for the Doubly An-Harmonic Oscillator Via Transformation to Bi-Confluent Heunas Differential Operators (Global Journal of Science Frontier Research, 2016)
Abstract not found
Keywords: heun’s; bi-confluent; schrodinger equation; super-symmetry; factorization